A phase 3 randomized, multicenter, double-blind study to evaluate the safety of upadacitinib in combination with topical corticosteroids in adolescent and adult patients with moderate-to-severe atopic dermatitis in Japan (Rising Up): An interim 24-week analysis - Norito Katoh; Yukihiro Ohya; Hiroyuki Murota; Masanori Ikeda; Xiaofei Hu; Kimitoshi Ikeda; John Liu; Takuya Sasaki; Alvina D. Chu; Henrique D. Teixeira; Hidehisa Saeki (2021)
Systemic atopic dermatitis treatments that have acceptable safety are needed.To evaluate the safety of the oral Janus kinase inhibitor upadacitinib in combination with topical corticosteroids (TCSs) for the treatment of atopic dermatitis.In this phase 3, double-blind study (Rising Up), Japanese patients (12-75 years) with moderate-to-severe atopic dermatitis were randomized in a 1:1:1 ratio to receive 15 mg of upadacitinib + TCS, 30 mg of upadacitinib + TCS, or a placebo + TCS (rerandomized in a 1:1 ratio to receive either 15 or 30 mg of upadacitinib + TCS at week 16). Adverse events and laboratory data were assessed for safety.In 272 treated patients, the serious adverse event rates were similar for 15- and 30-mg upadacitinib + TCS at week 24 (15 mg, 56%; 30 mg, 64%) but greater than those for placebo + TCS (42%). Acne (all mild or moderate; none leading to discontinuation) occurred more frequently with upadacitinib + TCS (15 mg, 13.2%; 30 mg, 19.8%) than with placebo + TCS (5.6%). Furthermore, herpes zoster infection (4.4% vs 0%), anemia (1.1% vs 0%), neutropenia (4.4% vs 1.1%), and creatine phosphokinase elevations (2.2% vs 1.1%) occurred more frequently with 30-mg upadacitinib + TCS than with 15-mg upadacitinib + TCS; none of these events were reported with placebo + TCS. No thromboembolic events, malignancies, gastrointestinal perforations, active tuberculosis, or deaths occurred.The limitations included a small sample size and short observation period as well as nongeneralizability of the results beyond Japanese populations.The results were generally consistent with those of previous reports; no new safety risks were detected.